The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.3171/foc.2009.26.2.e6
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord bypass surgery using peripheral nerve transfers: review of translational studies and a case report on its use following complete spinal cord injury in a human

Abstract: Spinal cord injury has been studied in a variety of in vitro and in vivo animal models. One promising therapeutic approach involves the transfer of peripheral nerves originating above the level of injury into the spinal cord below the level of injury. A model of spinal cord injury in rodents has shown the growth of peripheral nerve fibers into the spinal cord, with the subsequent development of functional synaptic connections and limb movement. The authors of this paper are currently developing a simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Nerve transfer surgery improves function in patients with PNI [15]. Extrapolation of this well-established surgical technique for those with cervical SCI is a valid approach to augment upper extremity function [68, 16, 23, 28, 36]. These preliminary results suggest that sacrifice of the brachialis, which is a redundant elbow flexor, does not significantly downgrade function in this uniquely vulnerable patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve transfer surgery improves function in patients with PNI [15]. Extrapolation of this well-established surgical technique for those with cervical SCI is a valid approach to augment upper extremity function [68, 16, 23, 28, 36]. These preliminary results suggest that sacrifice of the brachialis, which is a redundant elbow flexor, does not significantly downgrade function in this uniquely vulnerable patient population.…”
Section: Discussionmentioning
confidence: 99%
“…If electrically stimulated, they show contractions. Surgery in this case appears relatively timeindependent: a nerve transfer can switch motor control from a redundant and expendable donor to a muscle group distal to the lesion site bypassing the level of injury [32,33]. In this way, the functional motor units are reconnected to the central nervous system, potentially restoring volitional control.…”
Section: Timing For Surgerymentioning
confidence: 98%
“…Spinal cord bypass surgery using peripheral nerves[ 4 ], olfactory ensheathing cells[ 5 , 6 ] Schwann cells for transplantation[ 7 ] and neural stem cells (NSC)[ 8 ] have been performed. Studies in animals have shown improvements in injured spinal cord function when cells derived from the embryonic central nervous system of mice were transplanted[ 9 ].…”
Section: Introductionmentioning
confidence: 99%